Analisis Startegi Perencanaan Kebutuhan Bahan Baku Produk Box Panel Control - Ega Laksamana Putra (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2023)
The manufacturer's job is to distribute goods efficiently to meet consumer demand. If goods are delivered on time and are of acceptable quality and quantity, customers will be happy. As a result, a company's productivity levels can be greatly increased with a competent production system. This raises the issue that companies must be able to manage production schedules and prioritize client requests to avoid delivery delays, build excessive amounts of raw material inventory, and increase overall company profitability.